Play-based intervention to enhance executive function in young children with disabilities: A systematic literature review - RR Dina Kusuma Wardhani; RR DENI Widjayatri (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2025)
Executive function such as working memory, inhibitory control, and cognitive flexibility is crucial for early learning, yet children with disabilities often face delays. Play-based interventions are increasingly recognized as effective strategies for supporting executive function in inclusive early childhood settings. Guided by PRISMA 2020, the researchers systematically reviewed studies published between 2016 and 2025. Of 50 initially identified studies, 30 met final inclusion criteria after screening and appraisal (JBI, CASP; inter-rater reliability confirmed with Cohen’s Kappa). Studies were coded into three categories: analog, digital, and hybrid play models. Twenty seven of 30 studies (90%) reported significant executive function gains. Analog models (n=14) enhanced inhibitory control, cognitive flexibility, and self-regulation through social structures and play rules. Digital models (n=13), such as serious games, computer-based cognitive games, and digital storytelling. Hybrid models (n=3) integrated scaffolding and digital mediation strengthened working memory, inhibitory control, and emotion regulation; AR-enhanced storybooks in Indonesia showed notable effects. Analog play ensures ecological validity, digital tools deliver structured cognitive demands, and hybrid approaches demonstrably integrate both strengths, yielding broader and more transferable executive function benefits. This review contributes a taxonomy of executive function focused play interventions and highlights their alignment with inclusive ECE reforms in Indonesia. Future research should pursue rigorous RCTs, longitudinal designs, and curriculum integration to evaluate sustainability and scalability.Keywords: executive function; play-based intervention; analog; digital; hybrid